Neonatal tooth with Riga-Fide disease affecting breastfeeding: a case report - Jamani, Nurjasmine Aida; Ardini, Yunita Dewi; Harun, Nor Asilah (BioMed Central Ltd., 2018)
Background: Neonatal teeth erupt during the neonatal period and natal teeth are the presence of teeth since birth. While rare, natal teeth and neonatal teeth can have a significant impact on breastfeeding. Neonatal teeth are less common, and although its exact etiology is still unknown, it can cause difficulties in breastfeeding to the mother and may eventually lead to discontinuation of breastfeeding. Other associated possible complications include tooth aspiration and sublingual ulceration. This paper was aimed to discuss the clinical features, complications, and management of neonatal tooth, in addition to its impact on breastfeeding and role in sublingual ulcer formation. Case presentation: We present a baby girl who had a neonatal tooth with sublingual ulceration (Riga-Fede disease), which resulted in a difficulty to breastfeed for the baby and nipple pain to the mother. Following the extraction of the baby’s tooth, she immediately continued breastfeeding, and her tongue ulcer healed well. Conclusion: Extraction of the neonatal tooth promoted rapid healing of oral ulcers and the reestablishment of breastfeeding.